Pengaruh E-Commerce, Self Efficacy Dan Sistem Informasi Akuntansi Dalam Pengambilan Keputusan Berwirausaha - Muhammad Taufiq; Indrayeni Indrayeni (LPPM Universitas Dharma Andalas, 2022)
This study aims to obtain evidence regarding the effect of E-Commerce, Self-Efficacy and the use of accounting information systems on accounting student decision making for entrepreneurship.The data used is secondary data distributed to accounting students at Dharma Andalas University with a sample of 155 that selected based on purposive sampling. The data analysis technique is multiple linear regression. Based on the statistical tested, the results showed that self-efficacy and the use of accounting information systems influenced students' decisions to become entrepreneurs, while e-commerce did not affect students' decisions to become entrepreneurs. This research is expected to contribute to students in making decisions in entrepreneurship. Thus, they further improve their self-ability and accounting knowledge to become successful entrepreneurs.